2014
DOI: 10.1016/j.ijscr.2014.11.042
|View full text |Cite
|
Sign up to set email alerts
|

High grade angiosarcoma fifteen years after breast conservation therapy with radiation therapy: A case report

Abstract: HighlightsWe examine a case of secondary angiosarcoma of the breast fifteen years after original treatment.Introduction into secondary or radiation induced angiosarcoma of the breast.Discussion of the case reports for secondary angiosarcoma of the breast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Studies not reporting on women with RASB, double publications, and studies reporting on women with primary angiosarcomas were excluded. The 17 identified studies were retrieved in full and cross reference searching was performed and identified 58 further studies reporting on women with RASB [ 5 9 , 12 , 29 80 ]. Therefore, in summary, 75 studies were analyzed for this review.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies not reporting on women with RASB, double publications, and studies reporting on women with primary angiosarcomas were excluded. The 17 identified studies were retrieved in full and cross reference searching was performed and identified 58 further studies reporting on women with RASB [ 5 9 , 12 , 29 80 ]. Therefore, in summary, 75 studies were analyzed for this review.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The bulk of studies identified in this systematic review were small case series and case reports [ 7 , 8 , 13 44 , 46 63 , 65 67 , 70 , 72 – 80 ]. As expected, the heterogeneity among these studies with low numbers of RASB patients was considerable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Angiosarcoma tend to present 5–6 years, after breast-conserving therapy and subsequent radiotherapy [5] .…”
Section: Discussionmentioning
confidence: 99%